ENT 530 Case Study: Pink Daisy / Nurfathin Shahirah Veezar Efendy ... [et al.] - Veezar Efendy, Nurfathin Shahirah; Mohd Saiful Rahim, Siti Khadijah; Zairee, Nur Aina Syafiqah; Mad Daud, Zureen Haifa Dayana (2021)
Pink Daisy is a business that offers customized jewellery products to customers who want to surprise others without going out to the market. Pink Daisy was established from 2020 until now and chose Tik Tok and Instagram application as their strategic platform to start the business and promote the products. Based on observation, the price of the jewellery offered is affordable for the customer. The company’s vision is to build Pink Daisy as a well-known customized jewellery and her mission is to provide the best quality jewellery share the sustenance with other people